2012
DOI: 10.1007/s00405-012-2111-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngocutaneous fistula following total laryngectomy: multivariate analysis of risk factors

Abstract: The objective of this study is to establish the role of risk factors in the etiology of pharyngocutaneous fistula formation after total laryngectomy. A retrospective study was performed for patient, disease and treatment-related factors, and also factors related to pathology specimen. Logistic regression analysis revealed that fistula development ratio was 4.955 times higher in patients with fistula than in the control group when the preoperative hemoglobin value was below 12.2 g/dL, 3.653 times higher when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 20 publications
5
53
2
Order By: Relevance
“…This has been reported in other studies [22,23] and also in a meta-analysis [7], and there is speculation that it may be secondary to tissue contamination and/or larger tumor size [22]. We also identified hypothyroidism and low postoperative hemoglobin as risk factors for PCF, which have consistently been reported in other studies [7,13,14,19,23]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This has been reported in other studies [22,23] and also in a meta-analysis [7], and there is speculation that it may be secondary to tissue contamination and/or larger tumor size [22]. We also identified hypothyroidism and low postoperative hemoglobin as risk factors for PCF, which have consistently been reported in other studies [7,13,14,19,23]. …”
Section: Discussionsupporting
confidence: 87%
“…Preoperative radiation therapy increases both the frequency and severity of postoperative PCF [3,4,10,1315], and chemotherapy augments this effect [3,16,17]. Other factors associated with increased rates of PCF include patient comorbidities [8,10,18], hypothyroidism [13], low perioperative hemoglobin [7,19,20] and albumin [10,19], more advanced primary tumor stage [21], prior tracheotomy [7,22,23] positive surgical margins [24,25], concurrent neck dissection [7,15,18], shorter elapsed time from completion of radiation to surgery [15], and surgical closure technique [10,12,26]. Although it is generally accepted that previous radiation and chemoradiation increase the risk of PCF [27], there is little consensus regarding the relative significance of these other various factors.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, patients are at risk of pharyngeal stenosis or pharyngocutaneous fistula (PCF) formation, with reported rates ranging from 15.8% to 33% and 10.9% to 34%, respectively. These can lead to prolonged inpatient hospitalization, delayed onset of oral feeding, delayed initiation of adjuvant radiation therapy, and increased overall cost of treatment …”
Section: Introductionmentioning
confidence: 99%
“…Patient co-morbidities are consistently identified as a significant risk factor [2, 8, 12, 19, 20]. A systematic review and meta-analysis by Paydarfar and Birkmeyer [8] found prior tracheostomy, pre-operative radiotherapy, a low post-operative haemoglobin and concurrent neck dissection to be associated with higher rates of PCF [8].…”
Section: Discussionmentioning
confidence: 99%